PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MACROMEDIA FLASH UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KOGNITIF SISWA KELAS XI SMA NEGERI 1 JEROWARU - Khairul Aziz Anwar; I Wayan Karmana; Muli Harisanti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract: The initial observation of the researcher in SMA Negeri 1 Jerowaru shows the students 'learning interest is low, the students' learning result is less than the maximum and the method used by the teacher is less precise. Based on this research is done about the application of cooperative learning model type STAD assisted Macromedia Flash to improve motivation and student cognitive learning outcomes. The purpose of this study was to describe the STAD cooperative model type supported by Macromedia Flash in improving students' cognitive motivation and learning outcomes. Research subjects class XI IPA SMA Negeri 1 Jerowaru. The type of research is Classroom Action Research conducted two cycles, each cycle of two meetings. The approach in this study is a qualitative approach and a quantitative approach because it describes the state and data analysis. Student motivation data on cycle I reaches average 44,8 with medium category. In cycle II the student's motivation level increased, reaching 66,2 with high category. Student learning outcomes in cycle I the total number of completed students is 14 students with 70% complete thoroughness (not complete) then increased in the complete cycle II to 18 students, with 90% classical completeness (thorough). It can be concluded that the application of cooperative learning model type STAD with Macromedia Flash can improve motivation and cognitive learning outcomes of students of class XI SMA Negeri 1 Jerowaru